Histopathological and Radiographic Features of the Postoperative Osteolysis Surrounding the PLLA Pin After the Fixation of the Osteochondral Fragment for Osteochondral Lesion of the Talus. Issue 4 (16th October 2019) - Ikuta, Yasunari; Nakasa, Tomoyuki; Tsuyuguchi, Yusuke; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle, Arthroscopy, Basic Sciences/Biologics Introduction/Purpose: Several surgical options are available for the treatment of osteochondral lesion of the talus (OLT). Fixation of the osteochondral fragment could be performed for large lesions with the remaining articular cartilage surface of OLT. Bioabsorbable bone fixation devices, especially those made of poly-L-lactic acid (PLLA), can be used for fixation of the osteochondral fragment. Postoperative osteolysis surrounding the PLLA pins is occasionally observed; however, the significance and details of the event are not fully understood. This study aimed to elucidate the association among osteolysis surrounding the PLLA pins, histopathological findings of OLT, and preoperative computed tomography (CT) values of the pin fixation sites. Methods: This retrospective analysis included 20 patients with OLT (12 males and 8 females; mean age, 21.8 years). The tissue of the osteochondral fragment was intraoperatively collected using a bone biopsy needle. Subsequently, fixation of the osteochondral fragment was performed through the biopsy hole using a PLLA pin. Osteolysis surrounding the PLLA pin was assessed postoperatively by magnetic resonance (MR) imaging. The patients were then divided into an osteolysis and non-osteolysis group. Histopathologically, 5 parameters (trabecular bone loss, empty lacunae, inflammatory granulation tissue, cartilage like tissue, and osteoclast) were assigned scores of 1–3 points (negative, mild, and severe). The score was calculated as minimal (5 points) or maximal (15 points) via hematoxylin and eosin staining. The CT values around the pin insertion site on the postoperative MR images were measured using the region of interest on the preoperative CT images. The average values were calculated from consecutive 3 images. Results: Postoperative osteolysis and non-osteolysis surrounding the PLLA pin were observed in 9 and 11 patients, with a mean age of 22.8 and 21.0 years and a mean number of PLLA pins of 2.7 and 2.4, respectively. No significant differences were found between the two groups. Histopathological evaluation revealed that the osteolysis group had a significantly higher pathological score of 10.1 (SD, 2.0) than the non-osteolysis group, which had a score of 6.1 (SD, 1.0; P=0.0003). Preoperative CT images of the osteolysis and non-osteolysis groups showed mean CT values of 364.3 HU (SD, 78.0) and 463.6 HU (SD, 133.5) (p=0.054), respectively, on the coronal images, and 339.2 HU (SD, 64.2) and 467.8 HU (SD, 109.9) (p=0.0049), respectively, on the sagittal images. Conclusion: Intraoperative biopsy of the OLT allowed for histopathological evaluation in the same location as the site of PLLA pin fixation. Our findings suggest that the preoperative environments of the cancellous bone under the OLT affect osteolysis surrounding the PLLA pin postoperatively. Additionally, low preoperative CT values under OLT can assist in the prediction of osteolysis surrounding the PLLA pin, and another fixation method, such as a bone peg, should be considered for the fixation of the osteochondral fragment in these patients.